Stigma of Mental Illness in Germans and Turkish Immigrants in Germany: The Effect of Causal Beliefs - Von Lersner, Ulrike; Gerb, Julia; Hizli, Serdar; Waldhuber, Daniel; Wallerand, Anton Felix; Bajbouj, Malek; Schomerus, Georg; Angermeyer, Matthias C.; Hahn, Eric (Frontiers in Psychiatry, 2019)
Background: Stigma poses an additional burden for people suffering from mental illness, one that often impairs their social participation and can prevent them from seeking adequate help. It is therefore crucial to understand how stigma develops in order to counteract it by setting up effective evidence-based anti-stigma interventions. The present study examines the effect of causal beliefs on stigmatizing behavioral intentions, namely people’s desire to distance themselves from persons with mental illness. In addition, we draw cross-cultural comparisons between native Germans and Turkish immigrants to investigate the influence of culture on stigma and causal beliefs and to broaden knowledge on the biggest immigrant group in Germany and on immigrants in Western countries in general. Methods: n = 302 native Germans and n = 173 Turkish immigrants were presented either a depression or a schizophrenia vignette. Then, causal beliefs, emotional reaction and desire for social distance were assessed with questionnaires. Path analyses were carried out to investigate the influence of causal beliefs on the desire for social distance and their mediation by emotional reactions for Germans and Turkish immigrants, respectively. Results: We found an influence of causal beliefs on the desire for social distance. Emotional reactions partly mediated this relationship. Causal attribution patterns as well as the relationship between causal attributions and stigma varied across both subsamples and mental illnesses. In the German subsample, the ascription of unfavorable personal traits resulted in more stigma. In the Turkish immigrant subsample, supernatural causal beliefs increased stigma while attribution to current stress reduced stigma. Conclusion: Our study has implications for future anti-stigma interventions that intend to reduce stigmatization of mentally ill people. Targeting the ascription of unfavorable personal traits and supernatural causal attributions as well as promoting current stress as the cause for mental illness appears to be of particular importance. Also, the mediating influence of emotional responses to causal beliefs needs to be addressed. Furthermore, differential interventions across cultural groups and specific mental illnesses may be appropriate.